Edukasi Pijat Okstosin Dan Aromaterapi Lavender Sebagai Media Relaksasi Untuk Melancarkan Asi Pada Ibu Nifas - Fadjriah Ohorella; Rismawati Simbung (Pusat Riset dan Inovasi Nasional, 2022)
Mother's Milk (ASI) contains many substances and nutrients that are very beneficial for the growth and development of babies. Breast milk contains fat, protein, carbohydrates, vitamins and minerals that babies need. In addition, breast milk is also useful for forming the baby's body defense system so that it is not susceptible to diseases, such as diarrhea and pneumonia. Lavender aromatherapy is an inhalation method that uses aromatherapy, the positive impact of lavender aromatherapy has a relaxing effect on the central nervous system in the hypothalamus which helps increase the production of the hormone oxytocin which has an impact on increasing breast milk production. In addition to Lavender Aromatherapy which is able to provide a relaxing effect, one other alternative in providing a relaxing effect and being able to launch breast milk is the message relaxation method. Message is the most primitive pain therapy and uses human gentle reflexes to hold, rub, or squeeze painful body parts. It is hoped that with this health education activity the community, individual or group of breastfeeding mothers can find out how to massage oxytocin and use lavender oil and can be motivated to give exclusive breastfeeding to their babies so that their baby's growth and development can be maximized and change the mindset and motivation of mothers to give exclusive breastfeeding. with full awareness